Plasma extracellular nanovesicle (exosome)‐derived biomarkers for drug metabolism pathways: a novel approach to characterize variability in drug exposure. Issue 1 (16th November 2018) - Rowland, Andrew; Ruanglertboon, Warit; van Dyk, Madelé; Wijayakumara, Dhilushi; Wood, Linda S.; Meech, Robyn; Mackenzie, Peter I.; Rodrigues, A. David; Marshall, Jean‐Claude; Sorich, Michael J.
Abstract : Aims: Demonstrate the presence of cytochrome P450 (CYP) and UDP‐glucuronosyltransferase (UGT) proteins and mRNAs in isolated human plasma exosomes and evaluate the capacity for exosome‐derived biomarkers to characterize variability in CYP3A4 activity. Methods: The presence of CYP and UGT protein and mRNA in exosomes isolated from human plasma and HepaRG cell culture medium was determined by mass spectrometry and reverse transcription–polymerase chain reaction, respectively. The concordance between exosome‐derived CYP3A4 biomarkers and midazolam apparent oral clearance (CL/F) was evaluated in a small proof‐of‐concept study involving six genotyped (CYP3A4 *1/*1 and CYP3A5 *3/*3) Caucasian males. Results: Exosomes isolated from human plasma contained peptides and mRNA originating from CYP 1A2, 2B6, 2C8, 2C9, 2C19, 2D6, 2E1, 2 J2, 3A4 and 3A5, UGT 1A1, 1A3, 1A4, 1A6, 1A9, 2B4, 2B7, 2B10 and 2B15, and NADPH‐cytochrome P450 reductase. Mean (95% confidence interval) exosome‐derived CYP3A4 protein expression pre‐ and post‐rifampicin dosing was 0.24 (0.2–0.28) and 0.42 (0.21–0.65) ng ml –1 exosome concentrate. Mean (95% confidence interval) exosome CYP3A4 mRNA expression pre‐ and post‐rifampicin dosing was 6.0 (1.1–32.7) and 48.3 (11.3–104) × 10 –11 2 ‐ΔΔCt, respectively. R 2 values for correlations of exosome‐derived CYP3A4 protein expression, CYP3A4 mRNA expression, and ex vivo CYP3A4 activity with midazolam CL/F were 0.905, 0.787 and 0.832, respectively. Conclusions: Consistent strong concordance was observed between exosome‐derived CYP3A4 biomarkers and midazolam CL/F. The significance of these results is that CYP3A4 is the drug‐metabolizing enzyme of greatest clinical importance and variability in CYP3A4 activity is poorly described by existing precision dosing strategies.